Problem-Project based Learning Model for Improving Entrepreneurship Character and Reasoning Ability of Mathematics Education Students - Djafar, Suarti; Nurwijaya, Sugian; S., Putriyani (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2025)
Mathematics learning has not yet integrated students’ entrepreneurial character and reasoning abilities. In response, this study aimed to develop a Problem–Project Based Learning (PPjBL) model to strengthen both aspects within the Linear Programming course. The PPjBL model was developed using the Borg & Gall research and development framework through stages of design, validation, and classroom trials. The final PPjBL syntax consists of six stages: problem orientation, organizing students for learning, guiding investigation, designing the project, implementing the project, and documenting project reports. Results from expert validation and two implementation trials showed that the model is practical and effective. The entrepreneurial character of students improved from the “start to grow” to the “being habit”. Meanwhile, mathematical reasoning ability increased in the high category, indicating progress in problem formulation, logical construction, deduction, interpretation, and generalization. These findings affirm that PPjBL serves as a transformative pedagogical framework capable of integrating cognitive reasoning and affective character development through authentic learning experiences. The model positions students as active problem solvers through engagement with real-world entrepreneurial problems. Future research may extend the application of PPjBL to other mathematical domains, emphasizing the cultivation of critical thinking, creativity, and collaboration as integrated outcomes of holistic mathematical education.